Giant magnetoresistance by exchange springs in DyFe2/YFe2 superlattices - Gordeev, SN; Beaujour, J; Bowden, G; Rainford, B; de Groot, P; Ward, R; Wells, MR; Jansen, A (2001)
A report on the magnetization and magnetoresistance measurements for antiferromagnetically coupled DyFe2/YFe2 multilayers was presented. The formation of short range springs in the magnetically soft YFe2 layers was demonstrated which resulted in giant magnetoresistance. Both the magnitude of the effect and its dependence on magnetic field were found to be in good agreement with the theory of Levy and Zhang for domain wall induced giant magnetoresistance.